MICRONEEDLES: REVOLUTIONIZING TRANSDERMAL DRUG DELIVERY SYSTEMS - B., DEEPIKA; BEGUM, ANEES; KANDUKOORI, NAGA RAJU; MADHAV, KATLA VENU (International Journal of Applied Pharmaceutics, 2025)
Microneedles (MNDs) have emerged as a transformative technology in transdermal drug delivery, offering a minimally invasive alternative to traditional hypodermic needles. These microscale devices allow the direct delivery of medication into the dermal layers by creating tiny punctures in the skin. This article looks in-depth at the various types of MNDs, including hollow, hydrogel-forming, coated, dissolvable, and solid MNDs, along with the associated manufacturing techniques. These are used in many medical disciplines to reduce side effects, increase patient compliance, and enhance medication efficacy. Examples of these specialties include pain treatment, hormone administration, vaccine delivery, and cosmetic surgeries. Despite their promising advantages, problems with patient education, regulatory obstacles, and manufacturing scalability need to be fixed. This article describes the current status of MNDs technology, discusses potential changes in transdermal medication administration, and suggests future directions for study and development.